A novel PVDF/graphene composite membrane based on electrospun nanofibrous film for oil/water emulsion separation. (November 2016) - Yuan, Xiaoyu; Li, Wei; Liu, Haihui; Han, Na; Zhang, Xingxiang
Abstract: In this study, a new method to achieve high hydrophobic performance by coating polyvinylidene fluoride/graphene (PVDF/GE) composite membrane on the pristine PVDF nanofibrous film (NF) was explored. The GE in the PVDF solution plays a major role to the formation of double-tier composite membrane with such hierarchic micro/nanoscale structures. The incorporation of GE flakes into the polymer matrix improves the hydrophobicity of the membrane. GE, as crystal nucleus, is in favor of promoting the formation of the micro/nanoscale structures on the surface of membrane in the phase separation process. Various microscopy and crystallographic methods were used to evaluate the morphology characterization of the composite membranes. Furthermore, such high hydrophobic composite membrane may have potential to separate the water-in-oil emulsion and the flux of the membrane is over 150 kg·m −2 ·h −1 after 10 cycles. Highlights: The double-tier composite membrane was fabricated by coating polyvinylidene fluoride/graphene composite membrane on nanofibrous film. The nanofiber nonwoven with coral-like surface microstructure as a support layer was fabricated. The composite membrane could separate surfactant-stabilized water-in-oil emulsion easily.